2020
DOI: 10.1111/jomf.12711
|View full text |Cite
|
Sign up to set email alerts
|

Military Families' Stressful Reintegration, Family Climate, and Their Adolescents' Psychosocial Health

Abstract: Objective Grounded in the Contextual Model of Family Stress, this study sought to identify (a) how military families' postdeployment reintegration experiences relate to the psychosocial health of adolescents and (b) indicators of family climate as a linking mechanism. Background Reintegration requires individuals, families, and systems to readjust after a period of family disruption. Assessing reintegration is pivotal for understanding how military families are faring and what leverage points exist for enhanci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Family cohesion and support in military families tend to be characterized as protective factors for the family system and individual well-being and emotional stability (Russo & Fallon, 2015). Family support and family cohesion have been identified as correlates of depressive symptoms, self-efficacy, general well-being, and academic performance among samples of adolescents in U.S. Army families, such that adolescents who felt cared about and understood within their families tended to report better psychosocial outcomes (Arnold et al, 2017; O’Neal & Mancini, 2021).…”
Section: The Role Of Family In Adolescent Well-beingmentioning
confidence: 99%
“…Family cohesion and support in military families tend to be characterized as protective factors for the family system and individual well-being and emotional stability (Russo & Fallon, 2015). Family support and family cohesion have been identified as correlates of depressive symptoms, self-efficacy, general well-being, and academic performance among samples of adolescents in U.S. Army families, such that adolescents who felt cared about and understood within their families tended to report better psychosocial outcomes (Arnold et al, 2017; O’Neal & Mancini, 2021).…”
Section: The Role Of Family In Adolescent Well-beingmentioning
confidence: 99%
“…Research in the general population indicates that interparental conflict can disrupt children’s long-term outcomes, resulting in elevated emotional insecurity and internalizing and externalizing problems [ 29 ]. Although research with military families on this topic is rare, one recent study found that, during reintegration, interparental conflict was negatively related to youth’s self-efficacy and well-being and positively associated with their anxiety and depressive symptoms [ 30 ]. More positive youth outcomes are thus expected when there is less conflict, more constructive communication, and better cooperation between parents.…”
Section: Introductionmentioning
confidence: 99%